Navigating the Complexities of Advancing Human Rights in Madagascar: Persistent Challenges and Opportunities for Reform - Ratsimandisa Haritiana Zo; Rakotomalala Nivomboahangy Razanamiarisoa; Andrianjary Myriam; Razanadrasoa Vololonome Bodomalala; Ratiarimanajatovo Narindra; Ramiadamahefa Tojoniaina; Solofomiarana Rapanoel Bruno Allain; Robijaona Rahelivololoniaina Baholy (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2024)
The Universal Declaration of Human Rights, adopted in 1948, remains a powerful testament to humanity's collective commitment to dignity, freedom, and equality. Emerging in the aftermath of global atrocities, it provided a framework for the protection of civil, political, social, economic, and cultural rights. Although Madagascar was under French colonial rule at the time of its adoption, the country drew inspiration from its principles when drafting its post-independence constitutions. Despite the global recognition of these rights, violations continue to persist, both internationally and within Madagascar, where political crises have exacerbated human rights challenges. Torture, arbitrary detention, and extrajudicial executions still occur, though efforts at reform have been notable, supported by various national and international programs. Since independence, Madagascar has faced repeated cycles of political instability, marked by popular uprisings in 1972, 1991, 2002, and 2009. Each of these events contributed to the erosion of the country’s socio-economic fabric, culminating in the 2009 crisis, which led to widespread poverty and weakened state institutions. Although constitutional order was restored in 2013, reinforcing human rights remains an ongoing challenge. The legitimacy of power and public trust in political leadership, particularly in nations like Madagascar where democracy is an imitation of Western models, is tenuous. Fundamental freedoms, though enshrined in the Constitution, are not always fully realized, especially concerning freedom of expression. Media ownership, concentrated among political elites and business figures, has compromised media independence and pluralism. Additionally, the political participation of women remains hindered by the absence of affirmative action and political will. Nonetheless, there are opportunities to address these systemic issues. Strengthening gender equality, enhancing media pluralism, and ensuring adherence to human rights principles are essential steps toward sustainable development and the promotion of democracy in Madagascar.